Implementation of The Rights of People with Disabilities in Obtaining Employment for Graduates of Private Special Schools in Ciamis Regency - indriyani, indriyani; Qohar, Hendri Abdul (Journal of English Language and Education, 2025)
Abstract. This study aims to examine the implementation of employment rights for persons with disabilities, particularly among graduates of private Special Schools (SLB) in Ciamis Regency, Indonesia. This study used a qualitative approach with a case study design. The data collection techniques included observation, interviews, and documentation. The results show that although national regulations provide a strong legal basis, the practical implementation of employment rights remains limited owing to low societal perceptions, lack of multi-stakeholder synergy, and limited access to job information. Only approximately 18% of private SLB graduates managed to secure permanent jobs within one year of graduation. Therefore, more intensive collaboration between special schools, local governments, and business partners is needed to improve the economic participation of persons with disabilities.